Studi Kematangan Gonad Bulu Babi Di Kawasan Pantai Kecamatan Mesjid Raya, Kabupaten Aceh Besar - Nanda S. Putra; Widya Sari; Muhammadar Muhammadar (Jurnal Ilmiah Mahasiswa Kelautan Perikanan Unsyiah, 2017)
This study was conducted from November until December 2016. The location of the research implementation was in the beach area of Mesjid Raya District, Aceh Besar. The research method used was transect method. At each station, transect was made with the length of 25 meters and width of 10 meters. The transect rope was stretched with a5 meters distance from the perpendicular shoreline from the position of lowest tide point to the direction of the reef will. The measured parameters were the diameter of the shell body, the weight of the body, The Maturity Index of the Gonads (IKG) and The Maturity Level of the Gonads (TKG).TKG was determined based on the morphology of the gonads. Data were analyzed descriptively. The types of sea urchins found on the beach area ofMesjid Raya District in Aceh Besar Regency were Tripneutes gratilla, Echinothrix calamaris, Echinometra vanbrunti, Diadema setosum and Toxopneustes pileolus with a total of 66 individuals which comprised of 41 male urchin individuals and 25 female urchin individuals. All types of urchins can be found on theAhmad Rhangmanyang Beach with a total of 24 male individuals and 17 female individuals, whereas only three types of E. calamaris, E. vanbrunti, and D. Setosumcan be obtained from Lamreh Beach, with the total number of 17 male individuals and 8 female individuals. There was a diversity of gonads maturity between the individuals and the type of urchins that was found.       Penelitian ini dilaksanakan dari bulan November sampai bulan Desember 2016. Adapun lokasi pelaksanakan penelitian tersebut di kawasan Pantai Kecamatan Mesjid Raya, Aceh Besar. Metode penelitian yang digunakan adalah metode transek. Pada setiap stasiun dibuat transek dengan ukuran panjang 25 m dan lebar 10 m. Tali transek ditarik dengan jarak 5 meter dari bibir pantai yang tegak lurus dari posisi titik surut terendah ke arah tubir karang.Parameter yang diukur adalah diameter cangkang tubuh, bobot tubuh, Indeks Kematangan Gonad (IKG) dan Tingkat Kematangan Gonad (TKG).TKG ditetapkan berdasarkan morfologi gonad. Data dianalisis secara deskriptif.Jenis bulu babi yang ditemukan pada Kawasan Pantai Kecamatan Mesjid Raya Kabupaten Aceh Besar adalah Tripneutes gratilla, Echinothrix calamaris, Echinometra vanbrunti, Diadema setosum dan Toxopneustes pileolus dengan jumlah total 66 individu yang terdiri dari 41 individu bulu babi jantan dan 25 individu bulu babi betina. Seluruh jenis bulu babi tersebut dapat ditemukan di Pantai Ahmad Rhangmanyang dengan jumlah 24 individu jantan dan 17 individu betina,  sedangkan di Pantai Lamreh diperoleh hanya tiga jenis saja yaitu E. calamaris, E. vanbrunti, D. setosumdengan jumlah 17individu jantan dan 8 individu betina.Terdapat keragaman kematangan gonad antar individu maupun jenis bulu babi yang ditemukan.